Small flies - major problem - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The islands in the Pacific are ideally situated for exporting fresh fruit and vegetables to Australia, New Zealand, Japan, Canada and the United States. However, crops in all these countries are affected by fruit flies which reduce crop yields and...